Familial Interstitial Lung Disease Caused by Mutation of the STING1 Gene - Jinying Li; Jinying Li; Shuhua An; Zhongdong Du (Frontiers Media S.A., 2020)
Mutations that affect the STING1 (TMEM173) gene cause a rare autoinflammatory syndrome, which is known as STING-associated vasculopathy with onset in infancy (SAVI) and which was initially described in 2014 (1). Thus far, only four reports have been conducted regarding families affected with SAVI in the literature. In this article, the clinical, laboratory, and genetic characteristics of two generations (three cases) of SAVI are described. Unlike previously reported cases that were caused by STING1 mutation, the initial and major clinical manifestations of the mentioned cases are largely identified in the lungs with interstitial lung disease (ILD), and the evidence of typical extrapulmonary symptoms of early-onset systemic inflammation (e.g., cutaneous vasculopathy) were minimal except for the proband, who was diagnosed with arthritis 8 years after onset. In addition, a younger sibling showed no symptoms. Such reports are rarely related to mutations in STING1. The proband was examined with bronchoscopy and alveolar lavage to determine the cause. This study emphasizes that, in the clinical assessment of interstitial pneumonia in children, the possibility of STING1 mutation should be considered, especially in patients with arthritis in addition.